INLISLite dalam Manajemen Layanan Perpustakaan Sekolah - Maya Sri Rahayu; Asmendri Asmendri (Departement of Mathematics Education, 2023)
The management of special services in school libraries in general aims to provide smoothness to the learning process and to meet the needs of learners for learning reference sources. In order for the purpose of learning and education in schools to be achieved, the library plays an important role in supporting the implementation of learning to take place successfully. Library management must be planned, organized, and controlled so that library functions can be utilized optimally by providing excellent service to its users. The forms of services in the library are circulation services, reference services and information services. With the use of advances in library technology, it has an INLISlite automation system that makes it easier to manage library services. This research uses qualitative methods with literature studies as a data collection technique. This research is expected to be a reference for other libraries that have not implemented INLISlite automation.